Do entusiasmo ao alerta, do alerta ao incômodo: sentidos do som ferroviário - Fernandes, Karen Andressa (Universidade Federal de São Carlos, 2022)
The perception of sound is subjective in a way that the same sound can evoke different meanings, perceptions, and reactions in the individuals exposed to it. In the case of railway sounds, some conflicts have arisen from freight train traffic and mainly from the activation of the horn, an acoustic warning used to eliminate or minimize the risk of accidents: on the one hand, railway concession companies are obligated by safety standards to issue this early warning; on the other hand, portions of the population exposed to such sound feeling annoyed and harmed in terms of their environmental rights. Considering the safety in the face of the risks that the system offers and the emergence of environmental rights, we aim to describe the socio-environmental process that has made the relationship between railway traffic and some neighboring residents conflictive, focusing on a railway that cuts through the urban area of São Carlos city (São Paulo, Brazil). In that municipality, one of the emblematic expressions of this conflict is the opening of a civil inquiry by the Federal Public Ministry of São Carlos to ascertain whether noise pollution occurs due to the activities of the company responsible for rail traffic. From an interdisciplinary perspective, we combined bibliographic research with documental research to elucidate the socio-historical transformations of the relationship between the railway system and its sounds for the urban dwellers, followed by the mobilization of notions from Discourse Analysis. We demonstrate that the senses attributed to the railroad sound have a historical and sociological dimension linked to the changes in how citizens related to the railroad and how they interact with it today. The transition of senses about the railway system and its sounds has moved markedly from enthusiasm to nuisance in recent years, that is, from topophilia to topophobia. This process is a constitutive part of the metamorphoses in the risk society, in which different types of risks, disjunctions in the technical guidelines that intend to control them, and changes in the soundscape emerge.
From enthusiasm to alert, from alert to annoyance: railway sound senses
Keywords: Ruído ferroviário; Poluição sonora; Percepção ambiental; Modernidade reflexiva; História ferroviária; Railway noise; Noise pollution; Environmental perception; Reflexive modernity; Railway history; CIENCIAS HUMANAS::HISTORIA; CIENCIAS SOCIAIS APLICADAS::DIREITO; CIENCIAS SOCIAIS APLICADAS::DIREITO::DIREITO PUBLICO; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA; ENGENHARIAS::ENGENHARIA CIVIL::INFRA-ESTRUTURA DE TRANSPORTES::FERROVIAS; PROJETOS E CONSTRUCAO; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA URBANA